Analysis of the working accidents recordered during the harvesting of the trees, between 2013 – 2018, for workers of the National Forest Administration, Romsilva, Romania - MUȘAT Elena Camelia (Journal of Environmental Protection and Ecology, 2020)
Occupational health and safety is a priority for employers, especially due to the fact that, in most cases, non-compliance leads to serious health problems. Many of the forestry activities, and in particular those from logging wood, are characterised by a high degree of risk. Thus, one mistake is sufficient that can lead to less serious accidents, disability or even death. The research analyses the working accidents that occurred during the period 2013–2018 in the harvesting activities in public forests of state, managed by the National Forestry Administration. Data analysis shows that experience is not a decisive factor in avoiding injuries, and that, in large part, the deaths have been caused by the fall of dead or tensed trees. Starting from the existing data, the risk factors generating accidents at work were identified for the two categories of forest workers, respectively those who harvest the trees and those who drive the machinery. Also, it were determined the frequency of produced accidents and the seriousness of the consequences as a result of non-compliance with security measures. Thus, the aim of the study it was to find solutions to limit risk factors and to improve safety and health at work for the activities taken into consideration.
Keywords: health and securit; work accidents; harvesting; fatal accidents